Mechanical Performances and Microstructures of Cement Containing Copper Tailings - Zhang, Changsen; Zhou, Tingting; Wu, Qisheng; Zhu, Huajun; Xu, Peng (Asian Journal of Chemistry, 2014)
The physical and chemical properties of copper tailings have been investigated. The standardized mortars specimen, where cement was replaced by 5, 10, 15, 20, 25, 30 and 35 % of copper tailings were prepared. Its compressive and flexural strengths were tested, the microstructures were examined by scanning electron microscope and pore structures were investigated by mercury intrusion porosimetry. The results show that when copper tailings are less than 15 %, it can increase compressive strength and flexural strength and improve cement performances, while more than 15 % would go against the strength. The best mixing amount of copper tailings is 15 %. Therefore, copper tailings can be used as cement admixture to solve the problem of environmental pollution. It suggested that copper tailings can be recovered and recycled.